Preliminary analysis of wireless collaborative network on mobile devices - Abdullah, Natrah; Mustapar, Nur Amirah (Universiti Utara Malaysia, 2019)
Users are confronted with information overload when searching for information in virtual libraries. Studies claim that information overload leads to changes in the physiological signals of an individual which later results in decreased efficiency in information processing.There is a strong perception that when something changes, there is a moment in which the change occurs.The primary purpose of this research is to detect an indication at the moment of change occurring when searching in virtual libraries by focusing on the pattern reflected in physiological data that can potentially be used as a signal to convey information overload. This study adopted user test methods and methods from psychophysiology. The results from quantitative analysis were presented through graphs and tables. The results indicated that heart rate measurement was the best measure compared to other physiological measurements and the underlying pattern signalling information overload was presented in the form of a matrix. Recommendations for future work include using the pattern to design an application to monitor information load in individuals.